Refugees in Sweden During the Covid-19 Pandemic—The Need for a New Perspective on Health and Integration - Elisabeth, Mangrio; Maneesh, Paul-Satyaseela; Michael, Strange (Frontiers in Public Health, 2020)
Refugees are already a vulnerable group in society and are in a stressful situation due to their often uncertain legal status in seeking asylum and integration in the new society after migration. Refugees are, in general, at greater risk of poor health outcomes when contracting Covid-19, exacerbated by poor living conditions and difficulties in accessing healthcare. The longer-term social consequences of the pandemic also disproportionately impact refugees, including social isolation, unemployment, and difficulties to obtain correct health information. The aim of this paper is to review the social and health consequences that Covid-19 has brought to the refugees residing in Sweden. This needs to be emphasized in order to mitigate against these likely consequences and improve the overall well-being among such a highly vulnerable group in society. As Covid-19 demonstrates, human health needs to be understood holistically, meaning that the vulnerability of any individuals, or even nations, is a vulnerability for the whole population requiring urgent action.